Minimize Oil Losses in Palm Oil Mill through Optimalization of Sludge Separator Performance - Nabillah Nissya Fadhilah; Lisma Safitri; Ulil Albab Alfian; Nuraeni Dwi Dharmawati; Rengga Arnalis Renjani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
One of the most important clarification station engine parts for reducing oil loss is the sludge separator. The sludge separator uses high-speed centrifugal force to capture any oil that is still adhered to the sludge. This study aims to improve the working performance of sludge separator to minimize oil losses through variations in feeding rate, oil under flow and temperature of flow rate. The experiment was conducted at one of the palm oil mills in Central Kalimantan, with a capacity of 45 ton/h. Variations in sludge separator feed rates: 23, 25 and 27 tons/hour. Oil underflow variations: 5%, 6%, and 7%. Feed temperature variations are: 90°C, 93°C, and 95°C. Feed temperature variations:  90°C, 93°C, and 95°C. Based on research that has been done, using bait rate of 23 ton/h, temperature 90 °C, and oil underflows 5%, resulting in oil losses of 0.54% – 0.61%. This study has managed to lower oil losses in the sludge separator by 0.11 % and shows the level of stability below the standard that has been determined. Keywords:  Crude palm oil,  Oil losses,  Palm oil mill,  Sludge separator, Underflow